PENGARUH PARAMETER SPRAY GUN TERHADAP KEKILAPAN PADA PELAPISAN BAJA KARBON RENDAH (ST37) - Miftakhul Rohman; Mahros Darsin; Rika Dwi Hidayatul Qoryah (ROTOR, 2020)
Two purposes of painting of the automobile body, i.e. protection and aesthetic. For the aesthetic one, scientifically measured its glossiness. The purpose of this study was to determine the effects of painting parameters using a spray to its glossiness. Three parameters varied were: (i) comparison of paint composition and thinner (1:1.2; 1:1.4 and 1:1.6), (ii) spraying distance (110 mm, 130 mm and 150 mm), and air pressure (3.5 bar; 4.5 bar and 5.5 bar, while the glossiness measured in gloss unit (GU) using a gloss meter. The experimental design method used was the response surface method with Box-Behnken design. A series of tests were carried out prior to ANOVA and optimization with Minitab: (i) lack of fit test, (ii) simultaneous parameter test, (iii) the coefficient of determination test, (iv) identical test, (v) independent test and (vi) normal distribution test. Out of three parameters, the most influential one is composition with a coefficient of mathematical equation of 6.592. In this study, the highest value in the 10th trial was 57.3 GU which was occurred when the parameters used were: distance of 130 mm, composition 1: 1.6 and pressure 3.5 bar. On the contrary, the smallest value GU in the 7th experiment was 35 GU with a distance of 110 mm, composition 1:1.4 and pressure 5.5 bar. From processing data using Minitab, the maximum gloss value was 58.76 GU with distance 116.86 mm, composition 1: 1.6 and pressure 3.5 bar. Keywords: painting, Box-Behnken design, gloss meter